La perception des rectifications orthographiques de 1990 : quelle connaissance auprès des étudiants polonais - Lazar, Jan (2023)
The study is focused on the perception of the French spelling reform of 1990 by Polish students. The aim is to ascertain to what extent Polish students are familiar with the most recent spelling changes, which will also allow us to see if the new orthography is taught in the Polish cultural context. For this purpose, a linguistic survey among the students at the departments of Romance studies in Poland was conducted. The respondents were asked to write a dictation containing selected expressions which have had two possible spellings since 1990. The presentation of the obtained results is an integral part of this paper.
Keywords: orthography; perception; polish students